2019
DOI: 10.5539/jas.v11n15p181
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Nitrate Priming Increases the Germination Rate of Eggplant Seeds

Abstract: The priming may promote greater expression of the physiological potential of the seeds and contribute to the germination process under adverse environmental conditions. The objective of this study was to evaluate the physiological potential of eggplant seeds primed with different chemical agents and exposed to adverse temperatures. Seeds were subjected to priming with five chemical agents [unprimed (control); water (hydropriming); calcium nitrate (0.2%); amino acid L-phenylalanine (0.05%); L-phenylalanine (0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…In the present study primed seed with suitable concentration of salts and hydropriming (C2) showed better performance in respect to non-primed (C0) and other treatments. A number of studies showed similar enhancement strategy in germination and seedling establishment of crops in case of all the used mineral salts (Barbosa et al, 2016;Salles et al, 2019;Kumar et al, 2020;Choudhary et al, 2021).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In the present study primed seed with suitable concentration of salts and hydropriming (C2) showed better performance in respect to non-primed (C0) and other treatments. A number of studies showed similar enhancement strategy in germination and seedling establishment of crops in case of all the used mineral salts (Barbosa et al, 2016;Salles et al, 2019;Kumar et al, 2020;Choudhary et al, 2021).…”
Section: Discussionmentioning
confidence: 92%
“…: http://doi.org/10.53550/EEC.2023.v29i02s.061 S379 (Ibrahim, 2016). Ca(NO 3 ) 2 seed priming of crops potentiates the germination process, resulting in increase germination and radicle emergence rates (Salles et al, 2019). It also improves speed of germination, length of seedling, fresh and dry biomass of seedling and allows a greater expression of seed vigor in various crops (Barbosa et al, 2016;Gouveia et al, 2017;Maneesha, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The initial results demonstrate similarities in the effect of both calcium nitrate and potassium nitrate on seed conditioning for seedlings at 33 DAS. According to Salles et al (2019), the priming of eggplant seeds with calcium nitrate resulted in the highest germination rate of seeds and seedlings with the highest radicle emission rate. Calcium nitrate and potassium nitrate are salts that can release nitric oxide (NO), which are required in several physiological processes related to plant growth and development and provide resistance to abiotic stresses and resistance to pathogens (Sanz et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…The incorporation of chemical agents in the method of physiological conditioning of seeds (priming) is a way to guarantee vigorous seedlings (Kerbauy, 2013;Caixeta et al, 2014;Batista et al, 2015;Marcos Filho, 2015;. Nitric oxide, which is obtained using salts such as calcium nitrate and potassium nitrate, can be used to favor plant development and growth (Sanz et al, 2015;Salles et al, 2019). The effects of nitrate are related to several pathways in the initial germination processes and even in overcoming seed dormancy (Brasil, 2009;Kerbauy, 2013;Cardoso et al, 2015;Sanz et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…However, the difference between the 3 and 4 mM levels of Ca(NO 3 ) 2 in the control was not significant. The results of the various levels of calcium nitrate on the seed germination showed different responses (Salles et al 2019). Shabala et al (2006) suggested an extra mechanism of the calcium function in salinity-stressed plants:…”
Section: Interaction Between the Salinity And Calcium Nitrate On The ...mentioning
confidence: 99%